Comparing the predictive capability of self-report and medically-verified non-fatal overdose in adults released from prison: A prospective data linkage study. (1st January 2020) - Keen, Claire; Kinner, Stuart A.; Borschmann, Rohan; Young, Jesse T.
Highlights: Self-reported overdose history may miss people at increased risk of future overdose. Using medical records could identify further people at increased risk of future overdose. Data related to non-fatal overdose should be triangulated from multiple sources. Abstract: Background: Self-reported non-fatal overdose (NFOD) is a predictor of future overdose and is often used to target overdose prevention for people released from prison. However, the level of agreement between self-reported and medically-verified NFOD history remains unknown. This study aimed to determine the agreement between, and predictive value of, self-reported and medically-verified history of NFOD in people recently released from prison. Methods: Pre-release baseline survey data from 1307 adults in prison surveyed from 2008 to 2010 in Queensland, Australia were linked to ambulance, emergency department, and hospital records. We compared the agreement of self-reported NFOD history in the baseline survey and medically-verified NFOD ascertained through linked medical data. Unadjusted and adjusted regression models were used to determine the association between self-reported and medically verified NFOD history and medically-verified NFOD after release from prison. Results: 224 (19 %) participants self-reported NFOD history only, 75 (5 %) had medically-verified NFOD history only, and 56 (4 %) both self-reported and had medically-verified NFOD history. Compared to those with no NFOD history, those who self-reported and had a medical history of NFOD (adjusted hazard ratio (AHR) 6.1, 95 %CI 3.1–11.9), those with a medical history only (AHR 3.4, 95 %CI 1.7–7.0), and those who self-reported only (AHR 1.8, 95 %CI 1.0–3.5) were at increased risk of medically-verified NFOD after release from prison. Conclusions: Relying on self-report of NFOD is likely to miss people at increased risk of future NFOD, many of whom could be identified through medical records. Wherever possible, data related to NFOD should be triangulated from multiple sources.